WHAT EARLY HUSSERL CAN TELL US ABOUT MATHEMATICAL INTUITION. - Davidavičiūt, Rasa (Problems / Problemos)
The main objective of this article is to demonstrate that the utter rejection of Husserl's early philosophy of mathematics has been unjustified. More specifically, I argue that he anticipates both ones of the contemporary definitions and applications of mathematical intuition. In order to establish this I will first provide an analysis of the role of intuition in early Husserl's philosophy of mathematics and then show that it bears significant resemblance to the definition and application of intuition in the work of Charles Parsons, who is commonly credited as the flag-bearer of contemporary proponents of mathematical intuition.